Anomalous structures of the liver: an anatomical insight - K.W. Choy; S. Kogilavani; M. Norshalizah; S. Rani; A. Aspalilah; H.S. Farihah; O. Faizah; A.G. Norzana; S. Das (Societa Editrice Universo s.r.l., 2024)
Indexed by Scopus